Refractory Ventricle Arrhythmias Alternating with Pulseless Electrical Activity in a Young Woman Rescued by Extracorporeal Cardiopulmonary Resuscitation - Ilona Lálová; Lucie Filipovská; Hana Skalická; Ondřej Šmíd; Aleš Linhart; Helena Kollárová; Jan Bělohlávek (Case Reports in Medicine, 2018)
Introduction. Extracorporeal cardiopulmonary resuscitation (ECPR) is a challenging approach for treating refractory out-of-hospital cardiac arrest (OHCA). Case Presentation. The authors describe a case of a 40-year-old Caucasian female who suffered from refractory OHCA, was admitted to a hospital while receiving ongoing cardiopulmonary resuscitation, and was connected to venoarterial extracorporeal membrane oxygenation 73 minutes after collapse. Ventricular tachyarrhythmias alternating with pulseless electrical activity resolved after eight hours. Following complete cardiac and neurological recovery, only adenoviral genome was found in myocardial biopsy. After 11 months, another episode of identical arrhythmias was rescued by an implantable cardioverter-defibrillator. Conclusion. Adequate prehospital and early hospital logistics is a prerequisite for successfully implementing extracorporeal cardiopulmonary resuscitation for refractory OHCA.